DPSK OTDM Demultiplexing Using Flexible Pulse Clock from Raman Amplifier-Soliton Compressor - Irneza Ismail; Wan Zakiah Wan Ismail; Mus’ab Sahrim; Sharma Rao Balakrishnan; Kishi, N; Jamaludin J.; Rasedee, AFN (American Scientific Publishers, 2024)
Non-Indexed Publication